2. SHORT-TERM OUTCOMES OF RIGHT HEPATECTOMY FOR INTRAHEPATIC CHOLANGIOCARCINOMA IN THE DEPARTMENT OF HEPATOLOGY, VIETNAM NATIONAL CANCER HOSPITAL FROM 2017 TO 2022 (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the short-term outcomes of right hepatectomy for intrahepatic cholangiocarcinoma.Subject and method: This was a retrospective descriptive study of the cases who underwent right hepatetomy for intrahepatic cholangiocarcinoma at Department of hepatobiliary and pancreatic surgery in National cancer hospital from March 2017 to November 2022.Result: Elective surgery was performed for 27 patients. The average age was 60.2 ± 11.2 years, sex ratio was 1.25 male per 1 female; 18.5% of cases had a history of hepatolithiasis; hepatitis B and hepatitis C related: 68.3%. Elevated of CA 19-9 and CEA levels were seen in 77.8% and 55.6% of cases respectively. Anatomical right hepatectomy has the majority (81.5%); regional lymphadenectomy was performed in 11.1% of cases. Most of patients had the solitary tumor (51.8%) with its size being larger than 5cm (63%). Postoperative pathology: cholangiocarcinoma (81.5%), lymph node metastases (11.1%), IIIA TNM staging (66.7%). The mean operation time was 166.3 ± 55.4 min. Postoperative complications have the majority in pleural effusion (22.2%) and liver failure (14.8%). The classification of complications according to Clavien – Dindo were: I (66.7%), II (18.5%), IIIa (14.8%).Conclusion: Right hepatectomy for intrahepatic cholangiocarcinoma is a feasible, safe and effective method.
Keywords: Right hepatectomy, anatomical liver resection, intrahepatic cholangiocarcinoma.